Efektivitas fasad adaptif dengan mekanisme helicone terhadap nilai energi dan pencahayaan alami di Indonesia - Aldhi Nugraha Anantama; Agus Hariyadi (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The annual growth of energy consumption in both residential and public buildings has been established globally as been significantly increasing. Therefore, the proposed active and passive building designs are intended to provide convenience and greatly reduce the high energy requirements, before considering mechanical systems (associated with fossil fuel-based energy consumption). This encourages the development of a new design, such as the Climate Adaptive Building Shell (CABS). This study aims to assess the effectiveness of CABS with Helicone mechanisms on energy and natural lighting, as well as its influential factors. The parametric modeling simulation method was applied to compare the energy and natural lighting aspects, between the adaptive and static facades of the Helicone mechanism. The results indicated that the adaptive facade was more effective than the static, based on energy and natural lighting. It was also found that the 30° adaptive configuration with the Helicone mechanism was the most effective. These results were influenced by several factors, i.e., the small turning angle (30° and 150° (-30°) and the anticlockwise direction of the adaptive facade rotation.